2007
DOI: 10.1007/s10552-007-0122-2
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of myeloid leukemias and occupational pesticide exposure

Abstract: The strongest evidence of an increased risk of ML comes from manufacturing workers and pesticide applicators. Further studies will be needed to correlate reliable exposure data within these specific occupational groups with well-defined subtypes of leukemia to refine this assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 47 publications
1
45
0
2
Order By: Relevance
“…Indeed, in a recent systematic review, Van MaeleFabry et al [79] have found an increased risk of myeloid leukemia upon pesticide occupational exposure. In addition, prior meta-analysis [80,81] showed a relationship between farming and the occurrence of multiple myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in a recent systematic review, Van MaeleFabry et al [79] have found an increased risk of myeloid leukemia upon pesticide occupational exposure. In addition, prior meta-analysis [80,81] showed a relationship between farming and the occurrence of multiple myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…ORs and CIs are 2 commonly used estimators in most meta-analyses dealing with health risks associated with environmental chemical exposures. 12,13,15,[17][18][19][20][21] The results were compared and consensus was obtained before the meta-analysis.…”
Section: Data Extractionmentioning
confidence: 99%
“…Otros efectos de la exposición crónica a plaguicidas que presentan una contundente evidencia son las enfermedades neurológicas, como Parkinson, esclerosis lateral amiotrófica y Alzheimer(12,24-28) y el desarrollo de algunos tipos de cáncer como leucemia, cáncer de próstata y el linfoma de Hodgkin (12,(29)(30)(31)(32)(33)(34)(35). Las investigaciones han encontrado que existe un mayor riesgo de presentar estas enfermedades si se vive en áreas rurales, se bebe de agua de pozo y se trabaja en actividades agrícolas.…”
Section: El Problema Histórico De Los Plaguicidasunclassified
“…Los resultados concluyen, en una primera instancia, que los niveles de residuos de plaguicidas en vegetales de consumo nacional estarían dentro de la normativa vigente del MINSAL para esa épo-ca (1,33). Sin embargo, si se revisan detenidamente los datos, se puede observar que el 63% de las frutas y verduras consumidas en Chile contienen residuos de plaguicidas muy peligrosos.…”
Section: Efectos De Los Plaguicidas En La Poblaciónunclassified